ANALISIS AKTIVITAS MEREK MELALUI PLATFORM INSTAGRAM UNTUK MENINGKATKAN KEPEKAAN MEREK SANTIZ MOTOGARAGE - Widarman, Rizki Eka; Kusmayadi, Dicki (UM. Bengkulu, 2025)
The objective of this study is to examine how brand activities on Instagram, using an approach that leverages contemporary digital technology, can enhance brand awareness for Santiz Motogarage, an SME engaged in buying and selling used cars in Bandung. A descriptive qualitative research method was employed, and data were collected through interviews, observations, and documentation. The study shows that Santiz Motogarage’s brand activities—such as uploading product catalogs and videos—have significantly increased brand awareness. This was particularly evident after one of their videos featuring the ZX250R motorcycle went viral, generating an additional 56,000 views and gaining 1,000 new followers.However, key obstacles include inconsistency in content uploads, a lack of human resources, and competition from rivals. The study concludes that well-planned and consistent brand activities, along with a deep understanding of digital marketing strategies, can strengthen Santiz Motogarage’s brand sensitivity. Recommendations include increasing content consistency, leveraging the automotive community, and adopting customer-centric marketing strategies to build emotional connections with customers. Keywords: Brand Activity, Utilization of Contemporary Digital Technology, Brand Awareness, Digital Marketing